The Formation and Transformation of Korean Identity - Tomeyan, Anna (History and Culture, 2023)
The typology and understanding of Korean identity are considered in this article. Here we consider the transformation of Korean identity under the influence of historical process, especially the Japan’s policy of trying to assimilate the Korean nation to the Japanese and hinder the revival of Korean identity, and the loss of independence forced the Korean nation to undergo transformation of identity and absorb Western and modern values. We also consider Confucian values which are the basis of the Korean national identity. Korean identities are also analyzed here trying to reveal the similarities and features.